Detection and Genetic Environment of Pleuromutilin-Lincosamide-Streptogramin A Resistance Genes in Staphylococci Isolated from Pets - Deng, Fengru; Wang, Huiwen; Liao, Yifei; Li, Jun; Feßler, Andrea T.; Michael, Geovana B.; Schwarz, Stefan; Wang, Yang (Frontiers in Microbiology, 2017)
Increasing emergence of staphylococci resistant to pleuromutilins, lincosamides, and streptogramin A (PLSA) and isolated from humans and pets is a growing public health concern worldwide. Currently, there was only one published study regarding one of the PLSA genes, vga(A) detected in staphylococci isolated from cat. In this study, eleven pleuromutilin-resistant staphylococci from pets and two from their owners were isolated and further characterized for their antimicrobial susceptibilities, plasmid profiles, genotypes, and genetic context of the PLSA resistance genes. The gene sal(A) identified in 11 staphylococcal isolates was found for the first time in Staphylococcus haemolyticus, Staphylococcus epidermidis, and Staphylococcus xylosus. Moreover, these 11 isolates shared the identical regions flanking the sal(A) gene located in the chromosomal DNA. Two S. haemolyticus isolates from a cat and its owner carried similar vga(A)LC plasmids and displayed indistinguishable PFGE patterns. A novel chromosomal multidrug resistance genomic island (MDRGI) containing 13 resistance genes, including lsa(E), was firstly identified in S. epidermidis. In addition, vga(A)LC, sal(A), and lsa(E) were for the first time identified in staphylococcal isolates originating from pet animals. The plasmids, chromosomal DNA region, and MDRGI associated with the PLSA resistance genes vga(A), vga(A)LC, sal(A), and lsa(E) are present in staphylococci isolated from pets and humans and present significant challenges for the clinical management of infections by limiting therapeutic options.